Tuḥfat al-mulūk - Iṣfahānī, ʿAlī b. ʿAbī Ḥafṣ (Miras Maktoob, ISBN: 9789004365452., 2019)
In the Persianate world, wisdom literature has a long history, dating back to pre-Islamic times. After the advent of Islam, this type of literature, often enriched with Islamic, Greek, or Indian elements, was continued in various forms, be it in poetry, prose, or in a mixture of both. Some of these works would address themselves to a wider urban audience while others were primarily directed at kings and their immediate political entourage. Saʿdī's (d.691/1291-92) Rose Garden ( Gulistān ) is an example of the former, Niẓām al-Mulk's (d. 485/1092) Epistle on Rulership ( Siyāsat-nāma ) of the latter. A hybrid form is constituted by Naṣīr al-Dīn Ṭūsī's (d. 672/1274) highly influential Nasirean Ethics ( Akhlāq-i Nāṣirī ). Judging by its title, the work published here in a new edition would seem to be for kings only. But, compiled in the 6th/12th century, it is actually an account of the wisdom of kings that, written for a general audience.